1976
DOI: 10.1093/ajcp/65.6.991
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiologic Features of Human Candidiasis: A Common Deep Mycosis of the Brain, Heart and Kidney in the Altered Host

Abstract: In a review of 2,616 consecutive autopsies done at the University of Kentucky Medical Center over a 12-year period, 46 patients with complete postmortem examinations had tissue-verified candidiasis in two distinct patterns, with Candida albicans being most frequently cultured. Superficial candidiasis involving only lining surfaces was observed in 21 patients (46%). Usually, it complicated other lethal problems such as malignancy and bacterial sepsis. Nineteen of these patients (95%) had received antibiotics. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…Once in the bloodstream, C. albicans can infect a wide range of target organs, including the kidney, spleen, liver, heart, gastrointestinal (GI) tract, and lungs (58). Within target organs, invasive infections lead to significant tissue damage (59,60). One of the major problems in managing patients with HDC is the difficulty in establishing the diagnosis, because bloodstream Candida infections tend to present clinically with nonspecific symptoms similar to those seen with systemic bacterial infections (7).…”
Section: Class 2 (Damage Occurs In Hosts With Weak or Normal Immune Rmentioning
confidence: 99%
“…Once in the bloodstream, C. albicans can infect a wide range of target organs, including the kidney, spleen, liver, heart, gastrointestinal (GI) tract, and lungs (58). Within target organs, invasive infections lead to significant tissue damage (59,60). One of the major problems in managing patients with HDC is the difficulty in establishing the diagnosis, because bloodstream Candida infections tend to present clinically with nonspecific symptoms similar to those seen with systemic bacterial infections (7).…”
Section: Class 2 (Damage Occurs In Hosts With Weak or Normal Immune Rmentioning
confidence: 99%
“…DNA fragments containing the telomeric repeats are highly variable among different C. albicans strains. We have shown that the Ca3 repeat is relatively more stable and is suitable for use as a species-specific and strain-specffic probe for C. albicans.Candida albicans and related species are responsible for the majority of oral and vaginal yeast infections (la, 26) and continue to increase in frequency as a major cause of systemic infections in immunocompromised hosts (1,4,5,25,30). Because C. albicans and related species lack sexual cycles (46), genetic studies have been difficult.…”
mentioning
confidence: 99%
“…Candida albicans and related species are responsible for the majority of oral and vaginal yeast infections (la, 26) and continue to increase in frequency as a major cause of systemic infections in immunocompromised hosts (1,4,5,25,30). Because C. albicans and related species lack sexual cycles (46), genetic studies have been difficult.…”
mentioning
confidence: 99%
“…In mice, the organs most affected are the brain, heart and kidney; however, as the number of organisms used for challenge is reduced, the brain lesions remain almost constant in severity, whereas tissue damage in other organs becomes less obvious (66,67). A predominance of cerebral mycoses has also been reported to be a feature of the human disease as it occurs in endemic fungal areas in the United States (68), and in the immunocompromised host (69). The relevance of such models to mucocutaneous infections has been questioned, but such qualms may be groundless.…”
Section: Animal Modelsmentioning
confidence: 99%